PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - Tiffahani, Syifa Fairus (Departemen Matematika, 2023)
Problem solving ability is one of the goals of mathematics learning. However, activities learning are not optimal in facilitating students to improve their problem-solving ability. The test result show that the problem-solving ability was still low. One solution to overcome this is Think Talk Write cooperative learning model. The purpose of this study was to determine the effect of the Think Talk Write cooperatif learning model on the mathematical problem-solving ability of the VIII. This type of research was a quasi-experiment design with a non-equivalent posttest only group design. The population was all students of class VIII. Sampling was done by random sampling of class VIII.3 as the experimental class and VIII.2 as the control class. The instrument of this research is in the form of a problem-solving ability test. Based on the result of data analysis obtained P-value where P-value . It can be concluded that the problem-solving ability of students who study with the Think Talk Write cooperative learning model is better than students who learn with the direct learning model in class VIII SMPN 7 Padang. Keywords– Cooperative Learning, Direct Learning, Problem Solving Ability, Think Talk Write.